PENGARUH FREE CASH FLOW DAN INVESTMENT OPPORTUNITY SET TERHADAP KEBIJAKAN DIVIDEN DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL PEMODERASI: (Studi Kasus Pada Perusahaan Sektor Industri Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2018) - Muchammad Maftuhul Fahmi; Muhammad Sulhan (Universitas Putera Batam, 2020)
Dividend is one determinant factor level of shareholder. In determining dividend policy, the average company uses the free cash flow. On the other hand, when a company does not distribute dividends in that year, it is likely that the company will choose the long-term investment option in the form of investment opportunity set. Agency conflicts that arise between shareholders and managers to determine dividend policy can be overcome by increasing the level of company ownership. One of them is to increase the level of institutional ownership. The purpose of this study is to determine the effect of free cash flow and investment opportunity set on dividend policy with institutional ownership as a moderating variable. This research uses descriptive quantitative method. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange and which distributed dividends in a row from 2014 to 2018. The sampling method used in this study was the purposive sampling method and the resulting sample of this research were 24 companies. The data analysis of this research was processed using themethod Moderate Regression Analysis (MRA) with the help of SPSS software. The results showed that free cash flow had a significant positive effect on dividend policy. In addition, the investment opportunity set variable has a significant negative effect on dividend policy. While the level of corporate institutional ownership is not significant in moderating the relationship between the free cash flow variable and the investment opportunity set partially on dividend policy. Nevertheless, institutional ownership variables can have a strengthening effect in partially affecting the variable free cash flow and investment opportunity set on dividend policy.